DI-006 Analysis of activity 'questions/answers' about drugs in the pharmacy of a university hospital. (25th February 2017) - Raynaud, S; Marie-Daragon, A; Renon-Carron, F
Abstract : Background: In hospitals, the pharmacist has a key role in the optimisation of the appropriate use of drugs. Everyday, the help of the pharmaceutical team of the hospital pharmacy (HP) is requested by professionals of care services to answer many questions about drugs. This pharmaceutical questions/answers (PQA) activity is scarcely described in the literature, unlike other activities of clinical pharmacy such as prescriptions, collection of drugs or therapeutic training. Purpose: To measure and analyse this activity, we conducted a prospective study in the HP of a university hospital over 9 months. Material and methods: We collected the calls received by the HP team (pharmacists, juniors hospital pharmacists, pharmaceutical assistants). Data collection was done on tables in booklets, in each pharmacy service. The data collected calls were analysed by an Excel spreadsheet. Results: 212 questions were collected, mainly coming from the emergency department/intensive care unit and oncology, paediatrics and gerontology departments. More than 25% were about administration methods. Drugs from almost all therapeutic classification were represented, especially anti-infective drugs (21%). This study enabled us to make an assessment of the PQA activity and to create a computerised tool that can be used by all HP workers and permits them to gather all data that are available to answer a question previously asked faster. Conclusion: Many possibilities can be considered such as analysis of regular questions, communication with care services using existing tools (information notice, periodical of HP) and promotion of the activity using indicators of follow-up. Furthermore, the computerised database created from this study provides a real daily help to the pharmacist. These actions contribute to making the drug use process more safe. References and/or acknowledgements: Thanks to all the pharmaceutical team of the hospital pharmacy for participating in our study. No conflict of interest